Response of Xylem Ray Parenchyma Cells of Red Osier Dogwood (Cornus sericea L.) to Freezing Stress (Microscopic Evidence of Protoplasm Contraction). - Ristic, Z. (1994)
Freezing behavior of wood tissue of red osier dogwood (Cornus sericea L.) cannot be explained by current concepts of freezing resistance. Previous studies indicated that water in wood tissue presumably froze extracellularly. However, it was observed that xylem ray parenchyma cells within these tissues could survive temperatures as low as -80[deg]C and the walls of these cells did not collapse during freezing (S.R. Malone and E.N. Ashworth [1991] Plant Physiol 95: 871-881). This observation was unexpected and is inconsistent with the current hypothesis of cell response during freezing. Hence, the objective of our study was to further examine the mechanism of freezing resistance of wood tissue of red osier dogwood. We studied freezing stress response of xylem ray parenchyma cells of red osier dogwood using freeze substitution and transmission electron microscopy. Wood samples were collected in winter, spring, and summer of 1992. Specimens were cooled from 0[deg]C to -60[deg]C at 5[deg]C/h. Freezing stress did not affect the structural organization of wood tissue. However, the xylem ray parenchyma cells showed two unique responses to a freezing stress: protoplasm contraction and protoplasm fragmentation. Protoplasm contraction was evident at all freezing temperatures and in tissues collected at different times of the year. Cells with fragmented protoplasm, however, were noticed only in tissues collected in spring and summer. Protoplasm contraction in winter tissue occurred without apparent damage to the protoplasm. In contrast, protoplasm contraction in spring and summer tissues was accompanied by substantial damage. No evidence of intracellular ice formation was observed in parenchyma cells exposed to freezing stress. Differences in protoplasm contraction and appearance of cells with fragmented protoplasm likely indicated seasonal changes in cold hardiness of the wood tissue of red osier dogwood. We speculate that the appearance of fragmented protoplasm may indicate that cells are being injured by an alternative mechanism in spring and summer.